Inorganic fibers in lung tissue from patients with pleural plaques or malignant mesothelioma. - Mowé, Gunnar; Skaug, Vidar; Wannag, Axel (Scandinavian Journal of Work, Environment & Health, 1981)
The concentration of inorganic fibers in the lungs of patients with malignant mesothelioma and pleural plaques has been compared to that of patients without cancer or chronic respiratory diseases. The fiber concentrations have been determined by scanning electron microscopy and given as number of fibers per gram of dried tissue. A statistically significant difference in inorganic fiber content was found between the different groups.
Keywords: asbestos-related disease; inorganic fiber; lung; lung tissue; malignant mesothelioma; occupation; patient; pleural plaque; scanning electron microscopy